2019
DOI: 10.14309/ajg.0000000000000132
|View full text |Cite|
|
Sign up to set email alerts
|

Eradication Efficacy of Modified Dual Therapy Compared with Bismuth-Containing Quadruple Therapy as a First-Line Treatment of Helicobacter pylori

Abstract: OBJECTIVES: This study assessed the effectiveness, adverse events, patient adherence, and costs of modified dual therapy compared with bismuth-containing quadruple therapy for treating Helicobacter pylori infection in Chinese patients. We also sought to determine whether modified dual therapy could be used as an alternative first-line treatment for H. pylori infection. METHODS: A total of 232 H. pylori-infected, treatment-naive patients were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
157
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(168 citation statements)
references
References 35 publications
8
157
0
3
Order By: Relevance
“…The efficacy of a low-dose and/or less frequent dual therapy consisting of AMO (2.0 g/day or less) and PPI (twice/day or less) resulted in unacceptable eradication rates 32–34. Recently, high-dose and high-frequency dual therapy, defined as the administration of both AMO (≥2.0 g/day) and PPI (at least twice daily) for 14 days, has been reported to have greater H. pylori eradication efficacy as first-line therapy 35–38. However, side effects and poor patient compliance due to high dose, high administration frequency and long duration of treatment are the most common setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a low-dose and/or less frequent dual therapy consisting of AMO (2.0 g/day or less) and PPI (twice/day or less) resulted in unacceptable eradication rates 32–34. Recently, high-dose and high-frequency dual therapy, defined as the administration of both AMO (≥2.0 g/day) and PPI (at least twice daily) for 14 days, has been reported to have greater H. pylori eradication efficacy as first-line therapy 35–38. However, side effects and poor patient compliance due to high dose, high administration frequency and long duration of treatment are the most common setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 10 in a single‐center randomized controlled study conducted in mainland China in 2019 have reported the application of 14‐day dual therapy with esomeprazole (20 mg qid) and amoxicillin (750 mg qid) for treatment‐naïve patients (n = 116) and achieved relatively good eradication rates (87.9% in ITT and 91.1% in PP analyses). The eradication rates and compliance were similar to TPB therapy, but dual therapy had a lower incidence of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwan is a region of low antibiotic resistance, and the study results might not be generalizable to populations with high rates of antibiotic resistance. The other study is a single‐center randomized controlled study from mainland China, 10 and dual therapy (esomeprazole 20 mg and amoxicillin 750 mg) also achieved relatively good eradication rates of 87.9% in ITT and 91.1% in PP analyses. The eradication rates and compliance were comparable to triple plus bismuth (TBP) therapy (PPI, amoxicillin, clarithromycin, and bismuth), and dual therapy is associated with lower incidence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…This was significantly higher compared with the 10 days sequential therapy or 1‐week STT. A more recent paper from China compared the HDDT with the bismuth‐containing quadruple therapy for 2 weeks and showed an equivalent eradication rate of close to 90% for the HDDT regimen 20 . In another study from Taiwan, the HDDT achieved an eradication rate on ITT of 91.7% and was comparable to a non‐bismuth containing quadruple therapy 21 .…”
Section: Discussionmentioning
confidence: 99%